Follicular lymphoma cells induce T-cell immunologic synapse dysfunction that can be repaired with lenalidomide: implications for the tumor microenvironment and immunotherapy - Ramsay, Alan G. (American Society of Hematology, 2009)
An important hallmark of cancer progression is the ability of tumor cells to evade immune recognition. Understanding the relationship between neoplastic cells and the immune microenvironment should facilitate the design of improved immunotherapies. Here we identify impaired T-cell immunologic synapse formation as an active immunosuppressive mechanism in follicular lymphoma (FL) and diffuse large B-cell lymphoma (DLBCL). We found a significant reduction in formation of the F-actin immune synapse in tumor-infiltrating T cells (P < .01) from lymphoma patients compared with age-matched healthy donor cells. Peripheral blood T cells exhibited this defect only in patients with leukemic-phase disease. Moreover, we demonstrate that this T-cell defect is induced after short-term tumor cell contact. After 24-hour coculture with FL cells, previously healthy T cells showed suppressed recruitment of critical signaling proteins to the synapse. We further demonstrate repair of this defect after treatment of both FL cells and T cells with the immunomodulatory drug lenalidomide. Tissue microarray analysis identified reduced expression of the T-cell synapse signature proteins, including the cytolytic effector molecule Rab27A associated with poor prognosis, in addition to reduced T-cell numbers and activity with disease transformation. Our results highlight the importance of identifying biomarkers and immunotherapeutic treatments for repairing T-cell responses in lymphoma.